Society, economy and lordship in Devon in the age of the first two Courtenay earls, c. 1297-1377 - Burls, R (2002)
﻿ This thesis is a contribution to the social history of medieval Devon and the south- west in the lifetimes of the first two Courtenay earls, Hugh II (1275-1340) and Hugh III (1303-77). The fourteenth century was an era of particular importance to the region's social evolution, in which many sectors of the non-agrarian economy - cloth production, mining fishing, ship-building, intermational commerce - attained impressive levels of growth, interrupted perhaps only moderately by the demographic crises of the middle decades. Further encouragement to economic prosperity came from the war with France, which stimulated demographic and urban communities on the south coast and provided fresh opportunities for employment and personal advancement. Against this backdrop of economic change, the pattern of aristocratic power in the south-western peninsula was undergoing a fundamental transformation and shift in focus. Two great Anglo-Norman honors were united in 1297 under the Courtenays, giving a single aristocratic dynasty unprecedented influence and leverage over local society. Permanently resident in the county and led by vigorous personalities, the family rapidly became ubiquitous in all sectors of public life and the region experienced a quality and intensity of lordship rarely witnessed in the previous two centuries. The current work supplies a deficiency in the study of the medieval south-west, but also makes a case for extending the remit of a traditional county-based study to encompass a wider cultural and economic hinterland. Particular attention is paid to the influence of the physical landscape and geography on economic and seignorial development in medieval society. The thesis is divided into two parts: the first dealing with the economic and social infrastructure, and 'setting the scene' with a long-term historical survey; the second focusing specifically on the fourteenth century and placing a discussion of local power structures in a wider 'national' context.